Evaluation of treatment outcomes in ventricular septal defect closure through minimally invasive right axillary thoracotomy - Nguyen, Xuan Hung; Nguyen, Nhu Dat; Nguyen, Duc Dung; Nguyen, Nguyen Dang; Tran, Thanh Thai Nhan; Bui, Duc An Vinh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2026)
Background: Ventricular septal defect (VSD) is the most common congenital heart anomaly requiring surgical intervention. While median sternotomy remains the conventional approach, minimally invasive techniques through right axillary thoracotomy have emerged as viable alternatives offering superior cosmetic outcomes. This study aimed to evaluate the safety, feasibility, and early outcomes of VSD closure through minimally invasive right vertical axillary thoracotomy at our institution. Methods: A prospective descriptive study was conducted on 33 consecutive pediatric patients who underwent VSD closure through right vertical axillary thoracotomy at Hue Central Hospital from January 2025 to December 2025. Patients with isolated VSD (diameter ≥ 4 mm) were included. Patient demographics, operative parameters, postoperative outcomes, and echocardiographic follow-up data were collected and analyzed. Results: The study included 33 patients with a mean age of 28.0 ± 30.0 months (range: 1-97 months). VSD types were perimembranous (48.5%) and infundibular (51.5%). All procedures were completed without conversion to sternotomy. Mean cardiopulmonary bypass and aortic cross-clamp times were 49.2 ± 9.1 and 31.7 ± 7.9 minutes, respectively. There was no mortality, no complete heart block, and minimal complications (pneumonia 3.0%, pneumothorax 3.0%). Complete VSD closure was achieved in 87.9% at discharge, improving to 90.6% at one-month follow-up. Pulmonary artery pressure significantly decreased from 39.7 ± 18.5 mmHg preoperatively to 25.6 mmHg at follow-up. Conclusion: Minimally invasive VSD closure through right vertical axillary thoracotomy is a safe and effective approach with excellent early outcomes. The technique is applicable across a wide age spectrum and for both perimembranous and infundibular VSDs, offering substantial cosmetic advantages for pediatric patients.